1974
DOI: 10.1042/cs048195s
|View full text |Cite
|
Sign up to set email alerts
|

Central Sympathetic Transmitters and Hypertension

Abstract: 1. The aim of this presentation has been to review the current status of some central neurotransmitter mechanisms in the control of arterial blood pressure and in experimental hypertension. In addition, antihypertensive drugs with centrally mediated actions have been considered.2. There is ample evidence for a role of central noradrenaline mechanisms in central cardiovascular regulation. The catecholamine precursor, ~-3,4-dihydroxyphenylalanine, lowers blood pressure by activating sympatho-inhibitory noradrene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

1976
1976
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…The lower brain stem has been proposed as the primary site of * Present address: National Institute of Public Health, Pharmacology, Laboratory P.O.Box 1, 3720 BA Bilthoven, The Netherlands. action of the blood pressure lowering effect of L-dopa, a-methyldopa and clonidine (for review see Henning, 1973Henning, , 1975Van Zwieten, 1975;. It has been suggested that these drugs act by direct noradrenergic receptor stimulation and may mimic baroreceptor activation (Sinha et al, 1973;Schmitt et al, 1973;Haeusler, 1975;Kobinger and Pichler, 1975).…”
Section: Introductionmentioning
confidence: 99%
“…The lower brain stem has been proposed as the primary site of * Present address: National Institute of Public Health, Pharmacology, Laboratory P.O.Box 1, 3720 BA Bilthoven, The Netherlands. action of the blood pressure lowering effect of L-dopa, a-methyldopa and clonidine (for review see Henning, 1973Henning, , 1975Van Zwieten, 1975;. It has been suggested that these drugs act by direct noradrenergic receptor stimulation and may mimic baroreceptor activation (Sinha et al, 1973;Schmitt et al, 1973;Haeusler, 1975;Kobinger and Pichler, 1975).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, in view of the strong evidence implicating central NA in cardiovascular control (see Henning, 1975), the apparent sensitization of brain NA-receptors in hyperthyroidism may be related to the concomitant hyperkinetic circulation.…”
Section: Discussionmentioning
confidence: 96%
“…Development of complications is largely responsible for the 10 15% mortality rate in the early stage of AMI (Shah et al, 1994;Swan, 1991). Left ventricular dysfunction (Hendel, 1990), atrial fibrillation (Henning, 1975;Kannel & Abbott, 1987), supraventricular tachycardia (Henning, 1975), left bundle branch block (Henning, 1975), atrioventricular block (Tofler et al, 1987), recurrent ischemia, and reinfarction are common complications associated with in-hospital death.…”
Section: Discussionmentioning
confidence: 99%